Serum Hepcidin Predicts Uremic Accelerated Atherosclerosis in Chronic Hemodialysis Patients with Diabetic Nephropathy - Han Li; Su-Juan Feng; Lu-Lu Su; Wei Wang; Xiao-Dong Zhang; Shi-Xiang Wang (Chinese Medical Journal, 2015)
Background: Hepcidin, as a regulator of body iron stores, has been recently discovered to play a critical role in the pathogenesis of anemia of chronic disease. Atherosclerotic cardiovascular disease is the most common complication and the leading cause of death in chronic hemodialysis (CHD) patients. In the current study, we aimed to explore the relationship between serum hepcidin and uremic accelerated atherosclerosis (UAAS) in CHD patients with diabetic nephropathy (CHD/DN). Methods: A total of 78 CHD/DN and 86 chronic hemodialyzed nondiabetic patients with chronic glomerulonephritis (CHD/non-DN) were recruited in this study. The level of serum hepcidin-25 was specifically measured by liquid chromatography-tandem mass spectrometry. Serum levels of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) were measured by enzyme-linked immunosorbent assay. Results: High serum level of hepcidin-25 was seen in CHD patients. Serum hepcidin-25 in CHD/DN was significantly higher than that in CHD/non-DN patients. Serum hepcidin-25 was positively correlated with ferritin, high-sensitivity C-reactive protein (hs-CRP), TNF-α, and IL-6 in CHD/DN patients. CHD/DN patients exhibited higher common carotid artery intima media thickness (CCA-IMT), hs-CRP, and hepcidin-25 levels than that in CHD/non-DN patients. Moreover, in CHD/DN patients, CCA-IMT was positively correlated with serum hepcidin, hs-CRP, and low-density lipoprotein-cholesterol. On multiple regression analysis, serum hepcidin and hs-CRP level exhibited independent association with IMT in CHD/DN patients. Conclusions: These findings suggest possible linkage between iron metabolism and hepcidin modulation abnormalities that may contribute to the development of UAAS in CHD/DN patients.